35 m2 dwelling. notes to debate (2004)
This document analyzes the implications for Urban Design, after the resent resolution from MAVDT to reduce the construction area of Social Interest Dwelling (VIS) to 35 m2. Inasmuch the reflections regarding these fields have been subject to the architects, city planners, economists and loan entities view, it is crucial to assume a position from the Urban Design over the meaning of construction of a periphery city, to keep suitable conditions of habitability and sustainability for its inhabitants.